Clinicopathological profile and management of 161 cases of actinic cheilitis - Lopes, Maria Luiza Diniz de Sousa (An Bras Dermatol, 2015)
BACKGROUND: Actinic cheilitis (AC) is a potentially malignant disorder of the lip caused by chronic exposure to ultraviolet radiation from the sun. OBJECTIVES: To evaluate the clinical, demographic, morphological and therapeutic management in AC cases data associating to the histopathological grading. METHODS: Demographic, clinical and management data of 161 patients with AC were analyzed. In biopsied cases, two calibrated examiners performed histopathological grading by binary system. RESULTS: There was a prevalence of males (79.5%), aged 40 years or older (77.5%), light-skinned (85.7%), experiencing occupational exposure to sunlight (80.3%), with AC presenting clinically as white lesions (33.6%). Conservative treatment was adopted in 78 cases and biopsy in 83 cases (60.2% graded as low-risk AC). There were no significant associations between histopathological grading and gender (p= 0.509), age (p=0.416), ethnicity (p=0.388), occupational exposure to sunlight (p=1.000) or clinical presentation (p=0.803). CONCLUSION: This study reinforces the hypothesis that demographic and clinical characteristics of AC are not related to histopathological grading. Advice on protection from sun exposure should be encouraged to avoid progression of AC and invasive therapies.